Efforts to Improve Traffic Discipline Among High School Students by the Education and Training Unit of the Traffic Division, Tasikmalaya Police - Ikmawan, Dadan Ardika (Advances in Police Science Research Journal, 2024)
Transportation plays an important role in the human life system. The number of vehicles more and more years and the traffic violations are also increasing. The number of traffic violations conducted by high school students in the law area of Tasikmalaya Police is high enough to cause traffic accidents. The traffic accident in Tasikmalaya Resort Police jurisdiction in the last three years has increased. This research uses qualitative approaches and types of applied research. This research focuses on the efforts of the Unit of traffic of the Dikyasa units of Tasikmalaya Resort Police in an effort to increase the order of traffic in high school students with locations in the law area of Tasikmalaya Resort Police. This study discussed the problem using the theory of George R. Terry. The source of information on internal police and national police. Data collection techniques with obsevation, in-depth interviews, documentation. Test the validity of data using triangulation techniques. Data analysis by using data reduction, data presentation and withdrawal of conclusions. The results showed that the efforts of the Dikyasa Unit of the Tasikmalaya Resort Police traffic to increase the order of traffic in high school students using planning system, organizing system, implementation system, and control system. The inhibitory factor in the implementation of Dikmas, such as the quantity and competence of the personnel Unit Dikyasa, budget funds, facilities and infrastructure, students, and methods in the delivery of the Civil Education of the Traffic. Based on the results of the research, the authors suggested that Tasikmalaya Resor Police complete infrastructure, prepare an activity plan, increase the number of personnel and pay attention to the qualifications of personnel education qualification, and use an interesting method in delivering the activities Dikmas afterwards.